The TALE class homeobox gene Smed-prep defines the anterior compartment for head regeneration. - Daniel A Felix; A Aziz Aboobaker (PLoS Genetics)
Planaria continue to blossom as a model system for understanding all aspects of regeneration. They provide an opportunity to understand how the replacement of missing tissues from preexisting adult tissue is orchestrated at the molecular level. When amputated along any plane, planaria are capable of regenerating all missing tissue and rescaling all structures to the new size of the animal. Recently, rapid progress has been made in understanding the developmental pathways that control planarian regeneration. In particular Wnt/beta-catenin signaling is central in promoting posterior fates and inhibiting anterior identity. Currently the mechanisms that actively promote anterior identity remain unknown. Here, Smed-prep, encoding a TALE class homeodomain, is described as the first gene necessary for correct anterior fate and patterning during planarian regeneration. Smed-prep is expressed at high levels in the anterior portion of whole animals, and Smed-prep(RNAi) leads to loss of the whole brain during anterior regeneration, but not during lateral regeneration or homeostasis in intact worms. Expression of markers of different anterior fated cells are greatly reduced or lost in Smed-prep(RNAi) animals. We find that the ectopic anterior structures induced by abrogation of Wnt signaling also require Smed-prep to form. We use double knockdown experiments with the S. mediterranea ortholog of nou-darake (that when knocked down induces ectopic brain formation) to show that Smed-prep defines an anterior fated compartment within which stem cells are permitted to assume brain fate, but is not required directly for this differentiation process. Smed-prep is the first gene clearly implicated as being necessary for promoting anterior fate and the first homeobox gene implicated in establishing positional identity during regeneration. Together our results suggest that Smed-prep is required in stem cell progeny as they form the anterior regenerative blastema and is required for specifying anterior cell fates and correct patterning.